1986
DOI: 10.1227/00006123-198611000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy after Operation for Aneurysms

Abstract: The authors reviewed 100 consecutive survivors of aneurysm operations and identified 3 patients who developed postoperative epilepsy. The use of prophylactic phenytoin in the first 67 cases did not seem to influence the patient's risk of developing epilepsy. It is concluded that with present microneurosurgical techniques the risk of postoperative epilepsy is small and unselective use of phenytoin prophylaxis should be reconsidered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…A study of consecutive patients with aSAH (n = 100) who were followed for 4 years after surgery concluded that prophylactic phenytoin was not indicated, as only 3% of patients developed postoperative seizures, with no differences delineated in seizure incidence in patients with or without prophylactic AED use [26]. In another prospective study (n = 121) in which prophylactic AEDs were not utilized in surgically treated patients with aSAH unless they developed epilepsy ( ‡2 seizures), the overall risk for developing epilepsy was 7% and risk for a single seizure at 12 months was 2.5%.…”
Section: Incidence Timing and Predictors Of Seizures Following Asahmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of consecutive patients with aSAH (n = 100) who were followed for 4 years after surgery concluded that prophylactic phenytoin was not indicated, as only 3% of patients developed postoperative seizures, with no differences delineated in seizure incidence in patients with or without prophylactic AED use [26]. In another prospective study (n = 121) in which prophylactic AEDs were not utilized in surgically treated patients with aSAH unless they developed epilepsy ( ‡2 seizures), the overall risk for developing epilepsy was 7% and risk for a single seizure at 12 months was 2.5%.…”
Section: Incidence Timing and Predictors Of Seizures Following Asahmentioning
confidence: 99%
“…Younger age (<40 years old), loss of consciousness of >1 h at ictus, and Fisher Grade 3 were factors that were significantly associated with seizures. In this study, all patients were treated with prophylactic phenytoin until the first outpatient visit (2-3 weeks post-surgery), at which time the dose was tapered off if no late seizures had occurred [26].…”
Section: Incidence Timing and Predictors Of Seizures Following Asahmentioning
confidence: 99%
“…It was noted that middle cere bral artery aneurysms had the highest incidence of post operative seizures (35%) especially if there was an exces sive operative manipulation. These same investigators found that patients who underwent a combined transtentorial/translabyrinthine approach for vestibular schwan noma also had a higher incidence of postoperative epilep sy (22%) compared to 0% in patients treated via a translabyrinthine approach alone [12]. Operative brain injury, e.g.…”
Section: Discussionmentioning
confidence: 97%
“…As already noted, the location of the lesion may affect the incidence of postoperative seizures [1,3,8,27,32,33], Aneurysms located on the middle cerebral artery have a higher incidence of postoperative epilepsy when compared to aneurysms al other sites [1,33,34], How ever, when microsurgical approaches are used to expose intracranial aneurysms which minimize brain retraction, no association is found between the site of the aneurysm and the incidence of postoperative epilepsy [2,12], Tu mors that are located in the central regions, i.e., posterior frontal and anterior parietal, have a higher incidence of postoperative epilepsy than tumors in the frontal and temporal regions. Occipital lobe tumors have the least number of postoperative seizures [27], For anaplastic gliomas only, lesions in the frontal lobe have the highest incidence of postoperative seizures [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation